The interplay between copper metabolism and microbes: in perspective of host copper-dependent ATPases ATP7A/B - Zhou, Yixuan; Zhang, Leiliang (Frontiers in Cellular and Infection Microbiology, 2023)
Copper, a vital element in various physiological processes, is transported from the gastrointestinal tract to tissues and cells through diverse copper transporters. Among these transporters, ATP7A and ATP7B play significant roles in regulating systemic copper metabolism and exhibit precise regulation in their intracellular trafficking. These transporters undergo dynamic shuttling between the trans-Golgi network (TGN) and the plasma membrane via the endocytic recycling mechanism, which involves the retromer and other associated factors. Interestingly, the antimicrobial attribute of copper implies a potential connection between microbial infection and copper metabolism. Several microbes, Salmonella enterica, Cryptococcus, Influenza A virus (IAV) and Zika virus (ZIKV) have been observed to impact the regulatory mechanisms of ATP7A/B, either directly or indirectly, as a means of survival. This review summarizes the key features and trafficking mechanisms of the copper transporters ATP7A/B, and examines the intricate interplay between microbes and copper metabolism. Ultimately, it highlights how microbes can perturb copper homeostasis through interactions with host factors, offering valuable insights into the mechanistic aspects of host-microbe interactions.